The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00595-013-0803-2
|View full text |Cite
|
Sign up to set email alerts
|

The short- and long-term outcomes for patients with splenic flexure tumours treated by left versus extended right colectomy are comparable: a retrospective analysis

Abstract: Patients undergoing extended right or left colectomy for splenic flexure tumours seemed to have comparable short- and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 29 publications
6
52
0
Order By: Relevance
“…Pathological results were judged as satisfactory, with no R1 resection and 87% of the patients with more than 12 LNs harvested during the colonic resection. In our study, subtotal colectomy allowed the evaluation of a significant number of LNs, with a median of 20, which is more important than after left hemicolectomy, with an average between 12 and 20 harvested LNs in published series . After left hemicolectomy, the rate of surgical specimens with less than 12 LNs retrieved can reach up to 40%, which could result in understaging and a worse oncological outcome .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Pathological results were judged as satisfactory, with no R1 resection and 87% of the patients with more than 12 LNs harvested during the colonic resection. In our study, subtotal colectomy allowed the evaluation of a significant number of LNs, with a median of 20, which is more important than after left hemicolectomy, with an average between 12 and 20 harvested LNs in published series . After left hemicolectomy, the rate of surgical specimens with less than 12 LNs retrieved can reach up to 40%, which could result in understaging and a worse oncological outcome .…”
Section: Discussionmentioning
confidence: 76%
“…However, the authors did not exclude patients operated on in emergency, which represented half of the included patients. Furthermore, 10% of patients who underwent left hemicolectomy had a R1 resection, and the rate of local recurrence was 7% . More recently, de’Angelis et al reported a case‐matched study of 54 patients, treated by subtotal colectomy or left hemicolectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations